1999
DOI: 10.1023/a:1018912522342
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We have shown that the interaction between PAA and procaine HCl is dependent upon the presence of counterions (monovalent ions) and is mainly entropically driven. The calculated stoichiometry indicated that one procaine HCl molecule neutralised one carboxylic acid group on PAA. Although electrostatic interactions were necessary for initiating complex formation, the non-electrostatic forces were dominant in stabilising the PAA-procaine HCl complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
0
8

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(97 citation statements)
references
References 17 publications
5
84
0
8
Order By: Relevance
“…4,5,52 The BVC association rate in the PLGA nanocapsules was 75.8%, which is a very high value when compared to other studies reported in the literature for local anesthetics. [44][45][46][47][48] The stabilities of the NC polymer suspensions containing BVC were evaluated based on the physicochemical properties of size, polydispersity, zeta potential and association efficiency as a function of time (initial, 15, 60 and 120 days), with all the samples stored in amber glass flasks at room temperature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5,52 The BVC association rate in the PLGA nanocapsules was 75.8%, which is a very high value when compared to other studies reported in the literature for local anesthetics. [44][45][46][47][48] The stabilities of the NC polymer suspensions containing BVC were evaluated based on the physicochemical properties of size, polydispersity, zeta potential and association efficiency as a function of time (initial, 15, 60 and 120 days), with all the samples stored in amber glass flasks at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…[44][45][46][47][48] The stabilities of the NC polymer suspensions containing BVC were evaluated based on the physicochemical properties of size, polydispersity, zeta potential and association efficiency as a function of time (initial, 15, 60 and 120 days), with all the samples stored in amber glass flasks at room temperature.…”
Section: 552mentioning
confidence: 99%
See 1 more Smart Citation
“…A distribuição de tamanho e polidispersão foram medidas e expressas como média de 10 leituras. [16][17][18] Medidas de potencial zeta O valor de potencial zeta, dado em mV, foi determinado utilizandose o analisador de potencial zeta, Zeta plus ® (Malvern, UK). As análises foram realizadas diluindo-se (1/10 v/v) as suspensões de nanopartículas, sendo os resultados expressos como média de 10 leituras.…”
Section: Medidas De Tamanho E Polidispersãounclassified
“…A utilização de microscopia eletrônica, também associada à técnica de criofratura, permitiu evidenciar a organização morfológica de nanocápsulas de poli(cianoacrilato de etila), nas quais o óleo, um triacilglicerol (Miglyol 812 ® ), está circundado por uma parede polimérica 65 . Gouvender e colaboradores 68 , através de MET, mostraram que a incorporação de quantidades baixas ou elevadas de fármaco não alterou a morfologia de nanopartículas formadas por PLA-blocopoli(óxido de etileno). Santos-Magalhães e colaboradores 33 , através de MEV, verificaram a presença de uma segunda população de partí-culas, com cerca de 2 µm de diâmetro, em uma suspensão de nanocápsulas de PLGA, após 3 meses da preparação, a qual apresentava diâmetro inicial de 180 ± 52 nm.…”
Section: Avaliação Morfológicaunclassified